ANALISIS KASUS KEMATIAN RAWAT INAP DI RSAU dr. EFRAM HARSANA MAGETAN - Cahyawati, Nunuk; Djasri, Hanevi (Journal of Health Service Management, 2025)
Background : Patient mortality is one of the indicators of hospital service quality. Analyzing inpatient mortality is important to determine whether the death was due to a terminal illness and was justified or whether it could have been prevented with better and more advanced treatment so that corrective measures can be taken. Objective: Conduct a mortality audit at dr. Efram Harsana Air Force Hospital to determine strategies and efforts to improve the quality and management of patient services based on the results of the mortality audit. Method : The research method used in this research is the clinical audit method. The type of research used is a retrospective audit and this research uses a descriptive approach. Result and Discussion : The most common immediate cause of death was sepsis/shock sepsis (54.3%) and shock of other conditions (15.2%). The underlying causes of death were DM (21.9%) and stroke (20%). Unreasonable deaths accounted for 46.7% due to untimely diagnosis underlying disease (7.6%), inadequate treatment underlying disease (25.7%), untimely knowing cause of death (27.6%) and inadequate treatment of cause of death (37.1). Conclusion : Improvement efforts are aimed at timely recognition of sepsis/shock sepsis as a direct cause of death and the provision of adequate sepsis therapy.